Epidemiology of Monilinia laxa on nectarine and plum : infection of fruits by conidia - Fourie, Paul H. (Paul Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--University of Stellenbosch, 2001.